Culture, corruption, and the prospects for change A statistical study - Gonzales, Joseph I. B. (Quezon City University of the Philippines, 2009)
Abstract (Corruption, which has been linked theoretically and empirically to low levels of democracy and governance, and to economic underdevelopment, has been identified by leading international institutions as one of the principal economic problems, if not the foremost, of the Philippines. High levels of corruption in the Philippines have also been attributed to cultural factors. Using the World Value Survey WVS two-factor cultural construct, the study demonstrates strong associations among culture, corruption, and democracy and governance across various countries worldwide. Although confirmatory factor analysis of Philippine data validates the WVS two-factor cultural construct, factor analysis also reveals that alternative constructs are possible based on factor combinations that also account for a substantial proportion of variance in WVS data. Time series analysis forecast gradual improvement in democracy and governance ratings and a slight decline in corruption ratings for the Philippines. The study affirms that cultural is strongly related to corruption in ratings for the Philippines. The study affirms that culture is strongly related to corruption in the Philippines, and while acknowledging the capacity of individual political events and actors to directly affect the political situation, the study concludes, unfortunately, that any improvement is likely to be gradual. The study reveals patterns of statistical relationships among the variables under investigation, adding that a deeper understanding would be gained by combining qualitative with quantitative research methods. The relationship between culture and corruption in other bears further investigation because of its implication for the Philippines).
Thesis (M.S.) --University of the Philippines.